ransformation of the River Network within the Left Bank of the Middle Dnipro in the 19th-21st Centuries - Сарнавський, С.П.; Гребінь, Василь Васильович (Київський національний університет імені Тараса Шевченка, 2024)
The article provides a retrospective analysis of the transformation of the river system of the left tributaries of the Middle Dnieper during the 19th – early 21st centuries. based on the cartographic research method by overlaying maps of the corresponding time sections and satellite images (1985-2020). Based on this, the total length of the river network, the number of watercourses, and the density of the river network were calculated for the entire left bank of the Middle Dnieper as well as for key river basins. These rivers are the main source of water resources in agriculture, industry, housing and communal services, have significant hydropower potential, are actively used in recreational activities, fishing, to a lesser extent for river transport and are the most diverse part of the landscape with a combination of forest, meadow, steppe, swamp and coastal water natural complexes. Local water resources, calculated per 1 person, are 964 m³ of water per year, which is lower than the average for Ukraine. Therefore, studies of the rivers of the region are quite relevant in terms of the impact of economic use and the transformation of natural components as a result of global climate change. Based on the data obtained from the comparison of topographic maps of different ages of the 19th and 20th centuries, and satellite images of different years of the 20th and 21st centuries, a dynamic cartographic model of the transformation of the length and number of the river network of the left bank of the Middle Dnieper was created.

У статті здійснено ретроспективний аналіз трансформації річкової системи лівих приток Середнього Дніпра протягом XIX – початку ХХІ ст. на основі картографічного методу дослідження шляхом накладання карт відповідних часових зрізів та супутникових знімків (1985-2020 рр.). На основі цього обраховано загальну довжину річкової мережі, кількість водотоків, густоту річкової мережі в цілому всього лівобережжя Середнього Дніпра так і в розрізі ключових річкових басейнів. Досліджено зміни гідрографічної мережі лівобережжя Середнього Дніпра за останні 150-200 років. Відзначено значну інтенсивність трансформації гідрографічної мережі внаслідок зміни клімату та антропогенної діяльності. Особливо значні перетворення сталися в 1950-1970-ті рр. внаслідок будівництва Дніпровських водосховищ, будівництва ставків та водосховищ на лівих притоках Дніпра, що спричинило зникнення більше 500 водотоків в регіоні дослідження. Процес спрямлення та перетворення русел річок на систему осушувальних каналів також призвів до значних змін у річковій мережі. Загалом, за останні 150-200 років під впливом глобальної зміни клімату та людської діяльності було втрачено 3187 км довжини річкової мережі лівобережжя Середнього Дніпра. На основі отриманих даних співставлення різновікових топографічних карт ХІХ та ХХ століття, космічних знімків різних років ХХ та ХХІ ст. створена динамічна картографічна модель трансформації довжини та кількості річкової мережі лівобережжя Середнього Дніпра.
Трансформація гідрографічної сітки в межах лівобережжя Середнього Дніпра В ХІХ – ХХІ ст.
Keywords: річкова мережа; трансформація; Середній Дніпро; ліві притоки; кількість річок; довжина річок; густота річкової мережі; river network; transformation; Middle Dnieper; left tributaries; number of rivers; length of rivers; density of the river network